Hubungan Pola Makan Seimbang Dengan Kejadian Diabetes Mellitus di Wilayah Kecamatan Tabunganen - Sri Purwanti Ariani; Sri Jamilah; Baidah; Wayan Dani Karina (Journal of Mandalika Literature, 2024)
Diabetes Mellitus (DM) is a lifelong disease that cannot be cured, but blood sugar levels can be minimized or controlled to remain similar to those of individuals with normal glucose levels or within normal limits. Uncontrolled or poorly managed glucose levels can lead to various complications. The physical impact of diabetes includes patients becoming easily fatigued. Psychologically, patients may experience anxiety, stress, or even depression. Adjusting to a chronic illness like diabetes mellitus can cause stress (Basuki, 2014). Emotional stress negatively affects diabetes control because increased stress hormones can raise blood glucose levels, especially when food intake and insulin administration are not properly managed (Diabetes Mellitus, Diet, Balanced).